Transport and Economic Performance : Linkages and Implications for Sector Policy - Creightney, Cavelle D. (World Bank, Washington, DC, 2012)
Infrastructure's interactions with and importance to the economies of developing countries have not been fully understood. This is evident in the Bank's approach to sector work in infrastructure and in its structural adjustment programs, which emphasize adjusting prices to the detriment of a country's infrastructure. Still, the available evidence indicates that in poorer countries with inadequate infrastructure, imperfect markets, and a lack of capital, the aggregate supply elasticity of agriculture to non-price factors, such as public goods and services, is substantially greater than the response to prices. Research and policy analysis are needed to understand the way in which infrastructure affects economic performance and to examine how this should be taken into account in our policy interventions, both in infrastructure sectors and in overall macroeconomic management. The sub-Saharan African Transport Program (SSATP) is trying to help governments in sub-Saharan Africa improve their transport policies and programs and enhance the effectiveness and efficiency of the transport sector. It helps governments of sub-Saharan Africa define much needed policy reforms and assists with their implementation. This document is the first SSATP publication which addresses the relationship between transport and economic performance and considers the implications of these linkages for sector policy. It reviews the literature on the linkages between transport and economic performance.